Study on the influence of working condition variation on lubrication characteristics of EHA internal pump - Zhang, Yantao; Chen, Zongbin; Che, Jun; Liao, Jian (Scientific reports, 2025)
The operational characteristics of Electro-Hydraulic Actuator(EHA) result in the EHA internal pump facing complex conditions of variable speed, pressure and even direction, resulting in poor lubrication state of friction pairs. To study the evolution of lubrication states under varying working conditions, a joint simulation model using Simerics-MP+(Version: 5.2.13, https://www.simerics.com ) and MATLAB(Version: R2020a, https://www.mathworks.com/products/matlab.html ) was established, focusing on the gear ring/shell friction pair as the subject of study. The model was used to predict the micro-motion trajectory of the gear ring, and the results were validated through experimental measurements of dynamic changes. Results indicate that the simulation model can accurately predict oil film variations, with a calculation error of less than 7.6% for oil film thickness. The reduction in speed and the increase in load pressure will deteriorate the lubrication characteristics of the oil film in the friction pair. Under pump operating conditions, when the direction reversing rate increases from 20,000 rpm/s to 40,000 rpm/s, the average oil film thickness increases by 23.64%, while the fluctuation rate decrease by 2.57%. Similarly, when the direction reversing pressure decreases from 10 MPa to 5 MPa, the average oil film thickness increases by 22.39%, and the fluctuation rate decreases by 8.17%. During pump-motor working condition switching, an increase in the switching rate from 10,000 rpm/s to 40,000 rpm/s results in a 10.33% increase in average oil film thickness and a 20.9% decrease in fluctuation rate. This study significantly contributes to enhancing our comprehension of the evolutionary patterns of friction pairs in EHA internal pumps under varying operational conditions.